Research on Methods of Constructing Spatial Patterns of Historical and Cultural Protection and Charm in the Context of Territorial Spatial Planning—Taking Rikaze City as an Example - Yin, Hu; Gao, Ziting; Xu, Yang; Wang, Xiufeng (Journal of Progress in Civil Engineering, 2025)
In the context of territorial spatial planning, it is crucial to construct historical and cultural protection pattern and charm spatial pattern. In this paper, Rikaze City is selected as the research object, and the index evaluation system is constructed based on Rikaze's own ecological landscape resources, historical and cultural resources and tourism resources, and the evaluation results are applied to the construction of historical and cultural protection pattern and charm space protection and utilization pattern in the overall planning of national land space. The results show that the areas with higher quantitative scores of historical and cultural resources in Shigatse City are relatively patchy and have a strong correlation with the direction of historical routes. The areas with higher quantitative scores of natural elements are highly coupled with the distribution of nature reserves, and the areas with higher comprehensive scores of charismatic resources in the city area are characterized by piecewise and linear agglomeration and superposition. It is recommended to construct a regional historical and cultural protection pattern of “one corridor, two cities, six pieces and multiple points” and a spatial development pattern of “one corridor, four lines, five districts and multiple poles and cores”, which will be used to lead the city's historical and cultural protection and guide the development of tourism.